Integrasi Culturally Responsive Teaching (CRT) Dalam Penerapan Model Pembelajaran Problem Based Learning Untuk Meningkatkan Pemahaman Konsep Matematika - Pakpahan, Teresia Br; Siregar, Rosliana; Ramli, Amalia (LPPM Universitas PGRI Argopuro Jember, 2024)
This research aims to improve students' ability to understand mathematical concepts through the application of the Problem Based Learning learning model which is integrated with the Culturally Responsive Teaching (CRT) approach and the TaRL (Teaching at The Right Level) approach. This research is a classroom action research with the subject of students in class IX-7 UPT SMP Negeri 8 Medan for the 2024/2025 academic year, totaling 29 students. The research method used is PTK (Classroom Action Research) which in this case occurs in two cycles, with cycle I consisting of 1 meeting and cycle II consisting of 1 meeting. Each cycle is carried out with a focus on learning models and the ability to understand mathematical concepts. Based on the results obtained from the second cycle, there was an increase compared to the first cycle with the difference in the highest score in the first cycle being 9 students and in the second cycle being 16 students, the average score was 8 students while in the second cycle there were 10 students and The lowest score experienced a decrease, namely in cycle I there were 12 students while in cycle II there were 3 students. So the difference in the percentage of high scores in cycle I and cycle II is 27%. This happened by making improvement efforts by integrating the CRT approach and the TaRL approach which resulted in improvements in the observation aspect.